Correspondence primarily on Sir Charles Grandison (1750 - 1754) - Richardson, Samuel 1689-1761; Schellenberg, Betty A. 1956- (Cambridge Univ. Press, 2015)
"Samuel Richardson (1689-1761) was a highly regarded printer and influential novelist when he produced his final work of fiction, The History of Sir Charles Grandison (1753). Like his other novels, it was written in epistolary form, reflecting his lifelong interest in letter writing and the letter as a genre. Covering the period 1750-1754, many of these fully annotated letters are published from manuscript for the first time, or have been restored to their complete original form. Recording Richardson's relationships with leading cultural figures including Samuel Johnson, Colley Cibber and Elizabeth Carter, the volume reveals his support for other authors while struggling to complete his own 'story of a Good Man'. This publishing saga also incorporates Richardson's responses to the Irish piracy of his novel, and his exchanges with anonymous fans, including those who attacked the novel's tolerance for Catholicism and those who pleaded for a sequel"..
Keywords: Richardson, Samuel, -- 1689-1761 -- Correspondence; Richardson, Samuel, -- 1689-1761; Richardson, Samuel -- 1689-1761; Richardson, Samuel -- 1689-1761 -- The history of Sir Charles Grandison; Geschichte 1700-1800; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Novelists, English -- 18th century -- Correspondence; Briefsammlung -- 1750-1754